Praanggapan pada Dialog dalam Web Series Imperfect The Series dan Implikasi terhadap Pembelajaran Mengenal Teks Iklan di SMP - Yola Veronica; Linggua Sanjaya Usop; Lazarus Linarto; Yuliati Eka Asi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
The objectives of this study are (1) to describe existential presumption in the dialog in the web series “Imperfect The Series”. (2) Describing the factive presupposition in the dialog in the web series “Imperfect The Series”. (3) Describing lexical presupposition in the dialog in the web series “Imperfect The Series”. (4) Describing the nonactive presupposition in the dialog in the web series “Imperfect The Series”. (5) To describe structural presupposition in the conversational speech in the web series “Imperfect The Series”. (6) To describe the counterfactual presumption in the dialog in the web series “Imperfect The Series”. (7) To describe the implication for learning to recognize advertising text in junior high school. This research uses descriptive qualitative research. The data source in this research is obtained from conversational speech in the web series Imperfect The Series consisting of 12 episodes aired on WeTV Indonesia. The data collection techniques in this research are watching, listening, documentation, and note taking. Data validity uses data and method triangulation. Data analysis uses data reduction techniques, data presentation, and conclusion drawing. Based on the results of the research that has been conducted, there are 110 presumption data found. The six types of presupposition are: 1) Existential presumption consists of 55 data, 2) Factive presumption consists of 7 data, 3) Lexical presupposition consists of 33 data, 4) Non-active presumption consists of 6 data, 5) Structural presumption consists of 6 data, 6) Counterfactual presumption consists of 3 data.